PENGARUH KOMUNIKASI DAN FASILITAS TERHADAP KINERJA KARYAWAN PADA PT OSI ELECTRONICS - Denika Sarumaha; Wasiman (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The research aims to determine how communication and facilities influence the employees performance in PT Osi Electronics. The author conducts research on 131 employees at PT Osi Electronics who are respondents using the Slovin formula and sampling techniques using simple random sampling. The data analysis methods used are descriptive analysis, data quality tests, classic assumption tests, regression tests and hypotheses with the help of SPSS. The results of data analysis in this study showed that the communication is significant to the performance of employees with T count 14,835 > t table 1.978, the facility is negative and significant effect on the performance of employees with T count-3,253 < T table 1.978 and a significant value of 0.001 < 0,005 and communication and facilities simultaneously affect employee performance with F count 110,660 > F table 3.07. The results of analysis coefficient determinasi0,634 or 63.4%, which means the contribution of communication and facilities to the employee’s performance by the remaining 63.4% is influenced by other variables.